Sustainable Supplier Selection in the Chemical Industry Based on the Multi-Attributive Border Approximation Area Comparison (MABAC) Method - Fazrul Hamonangan Tanjung; Ari Pradana (Yayasan Sinergi Multidimensi Kreatif, 2026)
In supply chain management, supplier selection is recognized as one of the most critical and prominent purchasing functions, as it significantly contributes to enhancing a company's competitive strategy. Sustainability refers to an organization's ability to make real-time decisions without adversely affecting future environmental conditions, societal well-being, or business stability. Since the production of most chemical products is highly hazardous and has the potential to cause irreversible environmental damage as well as negative impacts on public health, sustainable supplier selection has become increasingly important. Therefore, this paper addresses this issue by proposing a multi-criteria decision-making (MCDM) framework for sustainable supplier selection in the chemical industry. Based on the specific characteristics of the chemical industry, this study employs the Analytic Hierarchy Process (AHP) to evaluate criteria across the economic, social, and environmental dimensions. Subsequently, the Multi-Attributive Border Approximation Area Comparison (MABAC) method is applied to rank the supplier alternatives. The proposed approach and decision-making model can assist sustainable supply chain managers in the chemical industry in selecting more sustainable suppliers, responding rapidly to market demands, and maintaining a high level of competitiveness in the marketplace.